2015
DOI: 10.3126/kumj.v11i2.12496
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Bifurcation of the Right Testicular Vein and Left Testicular Arterio-Venous Anastomosis

Abstract: The testis is the organ upon which the survival of the human species depends. Abnormalities of testicular vessels may lead to loss of gametogenesis and hormone production. Reported here is a case of bilateral variations of the testicular vessels observed in a male cadaver during the first year MBBS dissection classes. The right testicular vein bifurcated into two veins just before its termination and both the branches terminated into the inferior vena cava. The left testicular artery arose from the abdominal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…This anomaly might predispose to varicocele on right side. After detailed research of the literature, a case report by Nayak et al, [20] has been found regarding combination of abnormal termination of the right testicular veins in right renal vein and IVC both, as seen in [ [20] suggested that the right testicular vein develops from the lower part of the right sub cardinal vein. The terminal bifurcation of the right testicular vein might be due to the bifurcation of the right sub cardinal vein, during its development.…”
Section: Embryological Basismentioning
confidence: 99%
See 1 more Smart Citation
“…This anomaly might predispose to varicocele on right side. After detailed research of the literature, a case report by Nayak et al, [20] has been found regarding combination of abnormal termination of the right testicular veins in right renal vein and IVC both, as seen in [ [20] suggested that the right testicular vein develops from the lower part of the right sub cardinal vein. The terminal bifurcation of the right testicular vein might be due to the bifurcation of the right sub cardinal vein, during its development.…”
Section: Embryological Basismentioning
confidence: 99%
“…If the blood is shunted to the vein from the artery through this anastomosis, it might hinder the upward flow of blood in the vein, resulting in Varicocele. If the blood is shunted from the vein to the artery, that might result in lack of proper oxygen supply to the testis resulting in its decreased function or degeneration [20].…”
Section: Locale Of Drainagementioning
confidence: 99%
“…Variations in the terminations of the testicular veins have also been reported. Nayak et al [16], has found terminal bifurcation of the single right testicular vein into two, each opening into IVC. In another study, right testicular vein showed an abnormal termination in right renal vein instead of inferior vena cava [17].…”
Section: Methodsmentioning
confidence: 99%
“…Some isolated reports documenting gonadal vein anatomy[67891011121314151617] indicate the frequent occurrence of variations, which are not adequately described in the standard texts of anatomy. [1819] Few anatomical studies available have documented variations in western[5202122] and black[23] population.…”
Section: Introductionmentioning
confidence: 99%